Corporate Strategy and Tax Avoidance: The Mediation Effect of Profitability in the Dynamics of Transfer Pricing, Leverage, and GCG - Eko Budi Prasetyo; Rini Nur Anggraeni; Sekar Mayangsari (Institut Bisnis dan Informatika Kesatuan, 2026)
The background of this research is driven by the increasing practice of tax avoidance in Indonesia, particularly through transfer pricing mechanisms and the utilization of corporate financing structures. This study examines the effect of transfer pricing, leverage, and good corporate governance on tax avoidance in Indonesian food and beverage manufacturing firms. This study uses a quantitative approach with secondary data from companies’ financial statements for the 2020–2024. Based on the results, transfer pricing has an insignificant effect on tax avoidance and profitability, including its mediation through profitability. Leverage has an insignificant effect on tax avoidance and a significant effect on profitability, while its indirect effect on tax avoidance through profitability is not significant. Good corporate governance has a significant effect on tax avoidance, an insignificant effect on profitability, and no significant mediating effect through profitability. Profitability itself has an insignificant effect on tax avoidance. These findings highlight that corporate governance is a more decisive factor in promoting tax compliance compared to technical instruments such as transfer pricing and leverage in the food and beverage manufacturing sector. This study contributes to the development of tax policy, the strengthening of fiscal oversight, and the improvement of corporate governance implementation in Indonesia.